(3eYLe GdeUWdMGJ GdHQdeGfjI hGdOHdheGSjI (B:s (3Chd eYLe TGed aj cd GdeUWdMGJ GdHQdeGfjI hGdOHdheGSjI GdeJOGhdI hJYQjagG (B/s - (3GdeTGbHI, HSGe YHO GdQMefs ((3YeGf, GdCQOf (B:s (3OGQ CSGeI ddfTQ hGdJhRjY (B:s (3fHdGA fGTQhf hehRYhf,s, 2015)
(3LGA eYLe GdeUWdMGJ GdHQdeGfjI hGdOjHdheGSjI dJCUjd GdeUWdM GdHQdeGfj hGdOjHdheGSj, djVYg Ydi ScI GdeUWdMGJ GdeSJbdI Yf GdeUWdMGJ GdSjGSjI hGdbGfhfjI HYO Cf NVYJ GdeUWdMGJ GdHQdeGfjI hGdOjHdheGSjI NVhYG eHQeG ddeUWdM GdSjGSj, hef gfG aEf gPG GdeYLe LGA djYdf GSJbdGd GdeUWdM GdHQdeGfj hGdOjHdheGSj, djVY GdHGMKjf CeGe GdMbjbI GdLOjOI HGf GdeUWdM GdHQdeGfj gh eUWdM eSJbd ef MjK GdfXQ hGdYed(B.s
(3cTGa (B: (3UaMI (B363-392.s
(3HHdjhLQGajI (B: (3UaMI (B329-330.s
Keywords: (3GdYdhe GdSjGSjIs -- (3eYLe eUWdMGJs; (3GdgjFGJ GdJTQjYjIs -- (3eYLe eUWdMGJs; (3GdOHdheGSjIs -- (3eYLe eUWdMGJs